Analisis Resiko Waktu Di Proyek Konstruksi Studi Kasus Proyek Ampuh Pressure Maintenence Di Duri, Riau - Sukirno Sukirno (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2015)
Completion schedule some EPC project in Duri Riau in 2014 delayed. The condition always associated with risk in a certain scale. Risk analysis needed to reduce risks and solve the condition. Results of research conducted identify five major risks, namely human resource delays, material delays, the required equipmentsdelays, changes in design and specifications, and the lack of quality and the experience of supervision team. Fifth of risks identified in the high risk category. The level influence of risk to completion plan Ampuh Pressure Maintenance Project in Duri Riau with the probability 80% is 22,12% or 48 working days of the planned schedule 217 days is classified as high risk. After risk mitigation and control the probability 80% ,time delay decrease to 12.44% or 27 days.